New insights into the pathobiology of Down syndrome – hyaluronan synthase‐2 overexpression is regulated by collagen VI α2 chain. (28th March 2013) - Karousou, Evgenia; Stachtea, Xanthi; Moretto, Paola; Viola, Manuela; Vigetti, Davide; D'Angelo, Maria Luisa; Raio, Luigi; Ghezzi, Fabio; Pallotti, Francesco; De, Giancarlo; Karamanos, Nikos K.; Passi, Alberto
<x xml:space="preserve">Abstract</x> Down syndrome (DS) is a common birth defect characterized by the trisomy of chromosome 21. DS‐affected umbilical cords (UCs) of fetuses show altered architecture of the extracellular matrix. Overexpression of the chromosome 21 genes encoding the collagen type VI (COLVI) chains α1(VI) and α2(VI), COL6A1 and COL6A2, respectively, has also reported to occur in the nuchal skin of DS fetuses. The aim of this study was therefore to evaluate the COLVI content in euploid and DS‐affected UCs and human skin fibroblasts, and to investigate the relationships between COLVI and hyaluronan (HA) and HA synthase‐2 (HAS2). We found that the UCs of DS fetuses showed denser staining of COLVI and increased COL6A2 expression at both early and term gestational ages. In vitro expression studies in DS‐derived fibroblasts showed similarly increased amounts of α1(VI) and α2(VI) chains at the protein and transcriptional level, supporting the hypothesis of the gene dosage effect. Furthermore, increased levels of HA and HAS2 were also found in DS‐derived skin fibroblast cultures. Notably, silencing of COL6A2 in DS‐derived cells resulted in downregulation of HAS2, with a simultaneous decrease in secreted HA. Exogenous addition of COLVI to normal fibroblasts did not have any effect on HAS2 expression. In conclusion, UCs and skin fibroblasts in DS show significant increases in COLVI and HA; the overexpression of COL6A2 in DS tissue and cells is closely related to the increased expression of HAS2. These data may explain the DS phenotypes and their effects in organ tissue maturation.